Improving Students' Understanding Using Experimental Methods At SD Inpres Besakolka - Aprosina, Faot; Bahtiar, Yuyun (SCHOOLAR: Social and Literature Study in Education, 2024)
This increase was motivated by the finding that when science learning on human and animal organs was held at grade V SD Inpres Besakolka, it should not have reached 0.3% if 0.76% of students had not reached the KKM. So it is categorized as bad. Therefore, the purpose of this study is to improve students' understanding of human and animal organs through experimental methods. The implementation of cycle I was carried out on October 11, 2023, for improvement on cycle II on October 18, 2023. The data needed in this study were obtained through observation of discussions, observation of student and teacher activities, and formative tests. The analysis technique used was quantitative descriptive analysis, with the aim of determining student learning achievement. Based on the results of this study, it can be concluded that implementing the experimental method can improve student learning outcomes by reaching 23 students/88% who completed and 3 students/0.11% who did not complete in science learning on human and animal organs in grade V SD Inpres Besakolka students.